Prevalence of Epilepsy in Iran: A Meta-Analysis and Systematic Review - SAYEHMIRI*, Kourosh; TAVAN, Hamed; SAYEHMIRI, Fateme; MOHAMMADI, Iman; CARSON, Kristin V. (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Sayemiri K, Tavan H, Sayemiri F, Mohammadi I, Carson KV. Prevalence of Epilepsy in Iran : A Meta-Analysis and Systematic Review. Iran J Child Neurol. 2014 Autumn; 8(4):9-17. Abstract Objective Epilepsy is one of the most common diseases in Iran contributing to an array of health problems. In light of this, the aim of the present study is to examine the prevalence of epilepsy in Iran through a systematic review and meta-analysis. Materials & Methods A systematic search of several databases including PubMed, scientific information databases, Google, Google scholar, Elsevier and Scopus was conducted in June 2013. Observational studies were considered for inclusion if they were published in Iranian and examined epilepsy prevalence and/or related risk factors. Meta-analysis was conducted using a random effect model with the DerSimonian/Laird method. Heterogeneity was examined using the Breslow- Day test and inconsistency using the I2 statistic. Results A total of 45 studies were identified from the search strategy. Of these, nine published manuscripts with a total of 7,723 participants were included within the review. The pooled prevalence of epilepsy in Iran was estimated to be around 5% (95% confident interval (CI) 2 to 8). For each region the prevalence of epilepsy in central, northern and eastern Iran were 5% (95%CI 2 to 8), 1% (95%CI -1 to 3) and 4% (95%CI 3 to 11) respectively. The most common risk factors in order of prevalence were somatic diseases 39% (95%CI 15 to 62), convulsion 38% (95%CI 11 to 65), mental diseases 36% (95%CI 15 to 95) and hereditary development 26% (95%CI 9 to 42). A meta-regression model identified a declining trend in the prevalence of epilepsy within Iran for the last decade. Conclusion Pooled analyses from the nine included publications in this review estimate the prevalence of epilepsy in Iran to be around 5%. Although this result is much higher than rates in other countries, a declining trend in prevalence over the past decade was also identified. References 1. Valizadeh L, Barzegar M, Akbarbegloo M, ZamanzadehV, Rahiminia E, Ferguson CF. The relationship between psychosocial care and attitudes toward illness in adolescents with epilepsy. Epilepsy and Behavior 2013; 27: 267–271. 2. Widera E, LikusW, Kazek B, Niemiec P, Balcerzyk A, Aleksander L, Siero N, gak I. CYP3A5 * 3 and C3435T MDR1 Polymorphisms in Prognostication of Drug-Resistant Epilepsy in Children and Adolescents. Hindawi Publishing Corporation Biomed Research International 2013;12: 7 -10. 3. Koochaki E, Daneshvar R. Evaluation of Seizure Attacks in Patients with Cerebrovascular Accident. Zahedan J Res Med Sci 2013; 15: 29-32. 4. Asadi-PooyaA, Sharifzade M. Lennox–Gastaut syndrome in south Iran: Electro-clinical manifestations. Seizure 2012; 21: 760-763. 5. Motamedi M, Sahraian M, Moshirzadeh S. A Cross Sectional Study Evaluating Perceived Impact of Epilepsy on Aspects of Life. Zahedan J Res Med Sci 2012; 14: 33-36 6. Scott RA, Lhatoo SD, Sander J. The treatment of epilepsy in developing countries: where do we go from here? Bull WHO 2001;79:344–345. 7. Bharucha, N.E. Epidemiology of epilepsy in India. Epilepsia 2003;44: 9-11. 8. Ronnie D. Horner.Racial/ethnic disparities in the treatment of epilepsy: What do we know? What do we need to know? Epilepsy & Behavior 2006; 9: 243–264. 9. Nachvak M, Haghighat HR, Rezaei M. Prevalence and monitoring of retarded Childs in Tehran at 2002. Quarterly of science-research journal of Kermanshah University of Medical Sciences.2004; 3: 34-42. 10. Etemadifar M, Mirabdolbaghe P. Demographic and clinical characteristics of young epilepsy mortalities in Isfahan. Two quarterly of south pediatric, Persian golf center of health researches in Boushehr University of Medical Sciences. 2005; 2: 160-164. 11. Najafi MR, Rezaei F, Vakili Zarch N, Dehghani F, Barakatein M. Survey of pattern of personality and psychopathology in patients with Grandmal and complex partial epilepsy and comparison with control group. Journal of Shaheed Sadoughi University of Medical Sciences. 2010; 2:84-91. 12. Pashapour A, Sadrodini A. Grandmal epilepsy and EEG variations in primary school children at Tabriz. Medical Journal of Tabriz University of Medical Sciences. 2001; 50: 23- 27. 13. Mohammadi M, Ghanizadeh A, Davidian H, Mohammadi M, Norouzian M. Prevalence of epilepsy and co morbidity of psychiatric disorders in Iran. Seizure. 2006; 15: 476-482. 14. Nasehi M.M, Mahvalati Shamsabadi F, Ghofrani M. Associated Factors in Response to Treatment in Children with Refractory Epilepsy. J Babol University Med Sci (4):2010; 12: 61-66. 15. Kaheni S, Riyasi HR, Rezvani Kharashad MR, Sharifzadeh Gh, Nakhaei S. Prevalence of epilepsy in children at primary schools and awareness of teachers about epilepsy at primary schools of Birjand at 2010. Novel cares, Quarterly of science journal of nursing and midwifery in Birjand University of Medical Sciences. 2011; 3:135-142. 16. Rezaei AK, Saeidi Sh. Survey of starting age and gender of epilepsy and effective parameters on the Sina and Ghaem hospitals patients at 1989 till 1995. Rehabilitation magazine. 2000; 2: 52-57.